Improving the casting properties of high-strength aluminium alloys - Vojtěch, Dalibor (Materiali in tehnologije, 2004)
Al-Zn-Mg-Cu alloys are examples of high-strength alloys. After age-hardening they often possess tensile strengths of more than 500 MPa. However, their casting properties are relatively poor as a result of solidification intervals that are too wide. Therefore, they often require an extrusion, rolling, or forging treatment, and the production of small series of special parts can, as a consequence, be very expensive. In this study, an improvement in the castability and a reduction of the hot-tearing tendency was achieved byadding small amounts of appropriate elements (Ni, Mg and Si), which form a quasi-eutectic microstructure to reduce the solidification interval of the Al-Zn-Mg-Cu alloys. This improvement is demonstrated by a comparison of the casting properties of the quasi-eutectic Al-Zn-Mg-Cu-Ni-Si alloy with the AlZnsub7Mgsub2Cusub1 and AlSisub10 alloys. In addition, an appropriate heat-treatment procedure, which ensures the optimum mechanical properties, is described.
Keywords: aluminijeve zlitine; aluminium alloy; livnost; strjevanje